"NOSE" Validation in Portuguese and application in septoplasty - Alves, Sandra (2010)
Nasal obstruction is one of the most common symptoms, and septoplasty one of the most frequently performed surgeries in otorhinolaryngology. In order to evaluate the subjective response to septoplasty the AAO-HNS implemented the NOSE scale, developed and validated for North-Americans.The authors carried out the adaptation and validation of the NOSE scale for Portuguese language and population, allowing its further use in Portuguese studies. Subsequently, the validated Portuguese NOSE scale was employed in the evaluation of subjective results in a cohort of 100 patients that underwent septoplasty. A pre-operatory NOSE value of 74,6 was found, in contrast to 19,3 found in the post-operatory period.The results statistically confirmed the success of septoplasty in the improvement of nasal obstruction in patients with deviated nasal septum. The Portuguese NOSE scale confirmed to be a simple, rapid and reliable method for the evaluation of subjective nasal obstruction.